Tlr2/4 Double Knockout Attenuates the Degeneration of Primary Auditory Neurons: Potential Mechanisms From Transcriptomic Perspectives - Wang, Quan; Shen, Yilin; Pan, Yi; Chen, Kaili; Ding, Rui; Zou, Tianyuan; Zhang, Andi; Guo, Dongye; Ji, Peilin; Fan, Cui; Mei, Ling; Hu, Haixia; et al. (Frontiers in Cell and Developmental Biology, 2021)
The transcriptomic landscape of mice with primary auditory neurons degeneration (PAND) indicates key pathways in its pathogenesis, including complement cascades, immune responses, tumor necrosis factor (TNF) signaling pathway, and cytokine-cytokine receptor interaction. Toll-like receptors (TLRs) are important immune and inflammatory molecules that have been shown to disrupt the disease network of PAND. In a PAND model involving administration of kanamycin combined with furosemide to destroy cochlear hair cells, Tlr 2/4 double knockout (DKO) mice had auditory preservation advantages, which were mainly manifested at 4–16 kHz. DKO mice and wild type (WT) mice had completely damaged cochlear hair cells on the 30th day, but the density of spiral ganglion neurons (SGN) in the Rosenthal canal was significantly higher in the DKO group than in the WT group. The results of immunohistochemistry for p38 and p65 showed that the attenuation of SGN degeneration in DKO mice may not be mediated by canonical Tlr signaling pathways. The SGN transcriptome of DKO and WT mice indicated that there was an inverted gene set enrichment relationship between their different transcriptomes and the SGN degeneration transcriptome, which is consistent with the morphology results. Core module analysis suggested that DKO mice may modulate SGN degeneration by activating two clusters, and the involved molecules include EGF, STAT3, CALB2, LOX, SNAP25, CAV2, SDC4, MYL1, NCS1, PVALB, TPM4, and TMOD4.